ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DI PEMERINTAHAN DAERAH - Hendawati, Henda; Komarasakti, Dekrita; Ansori, Surya (Program Studi Akuntansi FPEB UPI, 2017)
Abstract. The purpose of this study was to evaluate the performance of a local government within the framework of fiscal decentralization. Â Regional financial ratios used are the ratio of independence, the ratio of effectiveness and efficiency, debt service coverage ratio, activity ratio, and growth ratio. The results of the calculation of financial ratios of Bandung Regency Government budget for 2010 â2016 fiscal year show local independence and higt local growth. Bandung Regency Government has been effective and efficient in using its income. The results of the evaluation in this study indicate that Bandung Regency Government is still dependent to Central Government in financing the activities. This condition shows that the welfare of the people is still low. Even though in the LAKIP Bandung Regency Government explained that it has been effective and efficient in managing finance, the number of funds in the budget balance with the central government increases every year.Keywords: government performance; Â regional financial ratio.Abstrak. Tujuan dari penelitian ini adalah untuk mengevaluasi kinerja pemerintah daerah dalam rangka desentralisasi fiskal. Rasio keuangan Daerah yang digunakan adalah rasio kemandirian, rasio efektivitas dan efisiensi, rasio debt service coverage, rasio aktivitas, dan rasio pertumbuhan. Hasil perhitungan rasio keuangan dari anggaran Pemerintah Kota Bandung untuk tahun fiskal 2010-2016, kemandirian dan pertumbuhan yang cukup tinggi. Pemerintah Kota Bandung telah efektif dan efisien dalam menggunakan pendapatannyaHasil evaluasi dalam penelitian ini menunjukkan bahwa Pemerintah Kota Bandung masih bergantung kepada Pemerintah Pusat dalam membiayai kegiatan pemerintahannya. Kondisi ini menunjukkan bahwa kesejahteraan rakyat masih rendah. Dalam LAKIP Pemerintah Kota Bandung menjelaskan telah efektif dan efisien dalam mengelola keuangan, jumlah dana dalam neraca anggaran dengan pemerintah pusat meningkat setiap tahun. Â Â Kata Kunci: pemerintahan daerah ; rasio keuangan daerah.Â